2021
DOI: 10.31234/osf.io/b3w24
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-dependent emotional memory transformation: divergent pathways of item memory and contextual dependency

Abstract: Emotional memory can persist strikingly long, but it is believed that not all its elements are protected against the fading effects of time. So far, studies of emotional episodic memory have mostly investigated retention up to 24h post-encoding, and revealed that central emotional features (items) are usually strengthened, while contextual binding of the event is reduced. However, even though it is known for neutral memories that central versus contextual elements evolve differently with longer passage of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…We also observed that memory retrieval was stronger during reexposure to the original encoding context than during exposure to a similar context. These findings replicate earlier studies (Cox, Meeter, et al, 2022;van Ast et al, 2013van Ast et al, , 2014, and show that our basic manipulations were successful. However, we did not find evidence for any of the hypotheses: reexposure to the original encoding context did not promote contextual dependency of memory, nor did exposure to a similar context reduce it.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We also observed that memory retrieval was stronger during reexposure to the original encoding context than during exposure to a similar context. These findings replicate earlier studies (Cox, Meeter, et al, 2022;van Ast et al, 2013van Ast et al, , 2014, and show that our basic manipulations were successful. However, we did not find evidence for any of the hypotheses: reexposure to the original encoding context did not promote contextual dependency of memory, nor did exposure to a similar context reduce it.…”
Section: Discussionsupporting
confidence: 91%
“…In short, inducing relatively strong reliving by reexposure to the encoding context was successful, and no other unexpected effects on reliving were observed. showing context-dependent memory (Cox, Meeter, et al, 2022;Godden & Baddeley, 1975; Smith & Vela, 2001;van Ast et al, 2013van Ast et al, , 2014, and smaller contextual dependency for emotional versus neutral memories (Cox, Meeter, et al, 2022;van Ast et al, 2013van Ast et al, , 2014.…”
Section: Manipulation Checksmentioning
confidence: 93%
See 2 more Smart Citations
“…The Statistical Package for the Social Sciences (SPSS) Version 25.0 (IBM Corp., Armonk, NY) was used to preprocess and analyze the data. The data and analysis code have been deposited at Open Science Framework (OSF) and are available at https://osf.io/ emxgv/ (Cox, 2021). The preprocessing and analyses strategies for the valence and arousal ratings, as well as the cued recall data (baseline and assessment of time-dependent effects), are also on https://osf.io/emxgv/ (described in supplementary materials).…”
Section: Discussionmentioning
confidence: 99%